Senile Systemic Amyloidosis: Clinical Features at Presentation and Outcome. Issue 2 (22nd April 2013) - Pinney, Jennifer H.; Whelan, Carol J.; Petrie, Aviva; Dungu, Jason; Banypersad, Sanjay M.; Sattianayagam, Prayman; Wechalekar, Ashutosh; Gibbs, Simon D. J.; Venner, Christopher P.; Wassef, Nancy; McCarthy, Carolyn A.; Gilbertson, Janet A.; et al.
Abstract : Background: Cardiac amyloidosis is a fatal disease whose prognosis and treatment rely on identification of the amyloid type. In our aging population transthyretin amyloidosis (ATTRwt) is common and must be differentiated from other amyloid types. We report the clinical presentation, natural history, and prognostic features of ATTRwt compared with cardiac‐isolated AL amyloidosis and calculate the probability of disease diagnosis of ATTRwt from baseline factors. Methods and Results: All patients with biopsy‐proven ATTRwt (102 cases) and isolated cardiac AL (36 cases) seen from 2002 to 2011 at the UK National Amyloidosis Center were included. Median survival from the onset of symptoms was 6.07 years in the ATTRwt group and 1.7 years in the AL group. Positive troponin, a pacemaker, and increasing New York Heart Association (NYHA) class were associated with worse survival in ATTRwt patients on univariate analysis. All patients with isolated cardiac AL and 24.1% of patients with ATTRwt had evidence of a plasma cell dyscrasia. Older age and lower N‐terminal pro‐B‐type natriuretic peptide (NT pro‐BNP) were factors significantly associated with ATTRwt. Patients aged 70 years and younger with an NT pro‐BNP <183 pmol/L were more likely to have ATTRwt, as were patients older than 70 years with an NT pro‐BNP <1420 pmol/L. Conclusions: Factors at baseline associated with a worse outcome in ATTRwt are positive troponin T, a pacemaker, and NYHA class IV symptoms. The age of the patient at diagnosis and NT pro‐BNP level can aid in distinguishing ATTRwt from AL amyloidosis.